An Examination of the Personality Constructs Underlying Dimensions of Creative Problem‐Solving Style. (27th November 2014) - Isaksen, Scott G.; Kaufmann, Astrid H.; Bakken, Bjørn T.
Abstract: This study investigated the personality facets that underpin the construct of problem‐solving style, particularly when approaching more creative kinds of problem‐solving. Cattell's Sixteen Personality Factors Questionnaire and VIEW—An Assessment of Problem Solving Style were administered to 165 students from the Norwegian Business School. We explored relationships through correlational and regression analysis. Personality profiles were derived for each of VIEW's three dimensions and were in generally expected directions. Those with an Explorer preference were more imaginative and idea oriented, open to change, unconventional, freethinking, and flexible than Developers. Those with a Developer preference were more practical and solution oriented, more traditional, rule conscious, conservative, and respecting of traditional ideas. Those with an External preference were more group oriented, affiliative, socially bold, warm, and attentive to others than those with an Internal preference. Those with a more Task‐oriented preference were more impersonal, detached, utilitarian, and tough minded than those with Person‐oriented preference. We outlined implications and suggestions for further research.